DNA hydrogel delivery vehicle for light-triggered and synergistic cancer therapy. Issue 21 (11th May 2015) - Song, Jaejung; Im, Kyuhyun; Hwang, Sekyu; Hur, Jaehyun; Nam, Jutaek; Ahn, G-One; Hwang, Sungwoo; Kim, Sungjee; Park, Nokyoung
Abstract : A drug delivery vehicle has been prepared by combining gold nanorods and a DNA intercalated drug in a DNA hydrogel, resulting in thermo-chemo combination therapy with photothermal-triggered DNA melting and release of doxorubicin. Abstract : A DNA hydrogel is reported as a delivery vehicle for gold nanorods and doxorubicin. The two photothermal and chemo cancer agents were co-loaded using electrostatic and DNA binding interactions, respectively. Light-triggered and highly synergistic combination cancer therapy was demonstrated in cellular and animal models.